Comparative Analysis of School Climate Perceptions in Public and Private Junior High School in Indonesia - Elfitra Lutfiah; Tina Hayati Dahlan; Nandang Budiman; Anne Hafina (Journal of Educational, Health and Community Psychology, 2026)
School climate plays a vital role in supporting students’ academic success and well-being, making it essential to explore how demographic factors influence their perceptions of the school climate. This study aimed to examine students’ perceptions of school climate based on demographic variables such as gender, age, grade level, and school type. Data were collected through convenience sampling from 482 junior high school students in Indonesia aged 11-17 years. The Indonesian version of the What’s Happening in This School? (WHITS) An instrument, which measures six dimensions of school climate, was employed. Reliability analysis indicated excellent internal consistency (α = 0.95). The results revealed no significant differences in school climate perceptions based on gender, age, or grade level. However, significant differences were found by school type, with students in private schools reporting a more positive school climate than those in public schools.